1998
DOI: 10.1080/004982598239597
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cytochrome P4503A4 as the major enzyme responsible for the metabolism of ivermectin by human liver microsomes

Abstract: 1. Ivermectin was extensively metabolized by human liver microsomes to at least 10 metabolites. The structure of many of them (mostly hydroxylated and demethylated) was determined by 1H-NMR and LC/MS. 2. To determine which human cytochrome P450 isoform(s) is responsible for the metabolism of ivermectin, chemical inhibitors including sulphaphenazole, quinidine, furafylline, troleandomycin (TAO) and diethyldithiocarbamate (DDC) were used to evaluate their effect on ivermectin metabolism. TAO, a specific inhibito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
85
0
3

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(93 citation statements)
references
References 5 publications
5
85
0
3
Order By: Relevance
“…In this study, a lack of a gender-effect was demonstrated in the in vitro liver drug metabolism of ivermectin, an antiparasitic macrocyclic lactone widely used in both veterinary and human medicine. This drug is known to be metabolised by CYP3A in man [61] whereas it might act either as a mild inducer of CYP3A in wild ruminants [53] or as a substrate of p-glycoprotein in the lamb [11]. Definitely more difficult to explain are the highest catalytic activities found in male PDM.…”
Section: Discussionmentioning
confidence: 95%
“…In this study, a lack of a gender-effect was demonstrated in the in vitro liver drug metabolism of ivermectin, an antiparasitic macrocyclic lactone widely used in both veterinary and human medicine. This drug is known to be metabolised by CYP3A in man [61] whereas it might act either as a mild inducer of CYP3A in wild ruminants [53] or as a substrate of p-glycoprotein in the lamb [11]. Definitely more difficult to explain are the highest catalytic activities found in male PDM.…”
Section: Discussionmentioning
confidence: 95%
“…This drug is extensively metabolized by human liver microsomes by cytochrome P450. The predominant isoform responsible for the biotransformation of this compound in the liver of humans is cytochrome P-4503A4, converting the drug to at least 10 metabolites, most of them hydroxylated and demethylated derivatives (23). In plasma, radioactive metabolites were reported after the oral administration of ivermectin to healthy volunteers (10).…”
Section: Eliminationmentioning
confidence: 99%
“…The specific agents chosen were HET0016, which is known to be a potent inhibitor of the CYP4 family of enzymes Sato et al, 2001), and ketoconazole and sesamin, both of which have been shown to inhibit CYP4F2-mediated tocopherol (vitamin E) metabolism (Ikeda et al, 2002;Sontag and Parker, 2002;You et al, 2005). Troleandomycin was chosen as a negative control, because it is a metabolism-dependent inhibitor of CYP3A4 (Zeng et al, 1998), an enzyme that is reportedly also inhibited by ketoconazole and sesamin (von Moltke et al, 2004); however, troleandomycin does not seem to inhibit CYP4F2 (Wang et al, 2006). HET0016, ketoconazole, and sesamin all substantially inhibited VK1 oxidase activity in HLM, exhibiting a 52 to 68% reduction in metabolite formation at the substrate and inhibitor concentrations tested.…”
Section: Lc-ms/ms Mrm Assay For Vk1 Metabolite Formation By Hlm Lc/esimentioning
confidence: 99%